Technical survey of the pathological problems of UEMG buildings – João Monlevade unit: effects and intervention conducts (Research, Society and Development, 2020)
This article has the objective to present a technical survey of building pathologies from Universidade do Estado de Minas (UEMG) – Unit João Monlevade. Pathological problems of the buildings were surveyed and the main causes and effects were pointed out according to technical literature. The pathologies were analyzed using the three basic steps of a methodology proposed by Lichtenstein, which consists of information collection, diagnosis and conduct definition. Building inspections, non-destructive tests to verifying the concrete degradation due to carbonation, Schmidt hammer test to determining the mechanical strength of the concrete were carried out. Besides the non-destructive tests, the maximum deflection of some system floors was determining to better understanding the occurred phenomena. The data collected in the survey were analyzed and the causes, correction and repair measures were defined to each studied pathology. The main identified pathologies were fissures in the masonry, excessive deformation of the system floors, carbonation, steel corrosion of reinforced concrete and infiltrations. An overview of the pathological problem analyses provides the confirmation that the most anomalies were associated to execution and/or design errors, allied to the lack of preventive maintenance of building elements.